Analysis of Raharja Services Compensation Claims Related to Traffic Accident Victims (Case Study of the Office of PT. Jasa Raharja Persero Rantau Prapat Branch) - Jodi Afrianto; Toni Toni (Budapest International Research and Critics University, 2022)
PT. Jasa Raharja (Persero) only provides compensation costs to victims of traffic accidents in the category of accidents between drivers except for single accidents that do not receive compensation costs. As for the type of qualitative research with a qualitative descriptive approach, the data in the field is adjusted to the laws and regulations. The results of the research conclusions after being obtained from the research object of PT. Jasa Raharja (Persero) Rantau Prapat Branch have run the Insurance Program according to the rule of law and can provide good service to the community. Meanwhile, the regulations for claiming compensation for traffic accident insurance are regulated in the Regulation of the Minister of Finance of the Republic of Indonesia Number. 16/Pmk.010/2017 Regarding Compulsory Compensation and Mandatory Contribution of Road Traffic Accident Funds, more detail is regulated in Article 4 Paragraph (1), (2), Article 4 and Article 5. Insurance against traffic accidents is very much considered by the Government.